![\tt Step-by-step~explanation:](https://img.qammunity.org/2021/formulas/mathematics/middle-school/1yvv69zlhkbxhn4v3cihgxbj4z92s81wn4.png)
![\tt Solve~for~y:](https://img.qammunity.org/2021/formulas/mathematics/high-school/yi9tnzuow7wd4zpul4rkr2w0ltvf0e8w1w.png)
To solve for y, we have to move all of the terms that do not equal to y on one side, and let y be on the other side alone. Do this by subtracting 3x on both sides to cancel it out from the left side and bring it to the right.
![\tt 3x-3x+y=-5-3x\\y=-5-3x\\y=-3x-5](https://img.qammunity.org/2021/formulas/mathematics/high-school/bqd9m6it41bfblga1ch2qpo88if70j72mw.png)
![\tt Solve~for~x:](https://img.qammunity.org/2021/formulas/mathematics/high-school/5iuni17qqh017mt89pjwjtdr1gozxsae55.png)
To solve for x, we will do the same thing we did to solve for y: move all the terms that do not equal to x to one side, and leave x on another side of the equation. We can do this by first subtracting y from both sides.
![\tt3x+y-y=-5-y\\3x=-y-5](https://img.qammunity.org/2021/formulas/mathematics/high-school/oh35xzdu55zv1td6jlxspzzjsltde1cg1e.png)
Then, we divide all terms by 3 to isolate the x.
![\tt (3x)/(3)=x\\\\ (-y)/(3)=(-y)/(3) \\\\(-5)/(3)=(-5)/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/1gmhpwl4a0gn1js473v0pd0pjh1dm2gqp7.png)
![\tt x=-(y)/(3) -(5)/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/z6epnzjcvw90w86i5ytjupt34tlk001b8a.png)
![\lare\boxed{\tt Our~final~answer:~y=-3x=5,~x=-(y)/(3)-(5)/(3) }](https://img.qammunity.org/2021/formulas/mathematics/high-school/iufy742lsub0dv4o9akyflmhtvgbjvvdho.png)